Polystichum caucasicum sp. nov. (Dryopteridaceae), a new, surprisingly hexaploid fern species from the Caucasus - Ekrt, Libor; Jessen, Stefan; Novák, Pavel; Vejvodová, Kateřina; Kalníková, Veronika; Lustyk, Pavel; Fraser-Jenkins, Christopher R. (Phytotaxa, 2025)
A new fern species, Polystichum caucasicum sp. nov., is described from the Caucasus region and adjacent areas of Georgia, Armenia, Turkey and Russia. The species was likely overlooked due to its morphological similarity to P. braunii and P. aculeatum, but it can be distinguished by a combination of characters, including a densely scaly rachis, enlarged basal acroscopic pinnules, and long-pointed pinnae. P. caucasicum could also be misidentified as P. kadyrovii in this region; however, a revision of the type material confirms that P. kadyrovii is conspecific with P. aculeatum and therefore not related to the newly described taxon. Genome size analyses (flow cytometry) of 20 individuals revealed an average 2C genome size of 44.7 pg, indicating a hexaploid cytotype, which is also supported by guard cell size measurements. In addition, a comprehensive comparative analysis of genome size characteristics was conducted across the majority of European and Caucasian Polystichum species, providing estimates of genome size, monoploid genome size (1Cx), and genomic GC content. The species produces well-developed fertile spores. Polystichum caucasicum appears to be an endemic of the Caucasus region and adjacent areas, growing in a wide ecological range in humus-rich and rocky beech, ravine or alluvial forests dominated by Acer, Fagus, Tilia and Alnus. Its habitat preferences are documented through four phytosociological relevés and realized climatic niche of the species at known locations was performed using the Chelsa Bioclim dataset.